AT THE EXECUTIVE COMMITTEE MEETING ON AUGUST 20, MANY QUESTIONS WERE ASKED ABOUT MINNESOTA - MOZINGO, ROGER (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Memorandum from Roger Mozingo to George Minshew and Michael Brozek regarding anti-tobacco sentiment in Minnesota. Lists actions needed including: preparing a report of government officials to explain why Minnesota is particularly anti-tobacco, outline all current efforts in the state, and lastly analyze tobacco industry resources in the state and how they can best be used to allow tobacco to survive in such a climate.